PENGARUH PENGEMBANGAN KARIR DAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN PT POS INDONESIA (PERSERO) BEKASI - Widya Parimita; Laysa Aneu Afrilla Wahda; Agung Wahyu Handaru (Jurnal Riset Manajemen Sains Indonesia, 2015)
The purpose of this study were: 1) to know the overview of career development, motivation, and job satisfaction the employee at PT Pos Indonesia (Persero) Bekasi. 2) To know the influence of career development on job satisfaction. 3) To know the influence of motivation on job satisfaction. 4) To know the influence of career development and motivation simultaneously on job satisfaction. Research carried out by the simple random sampling method on 154 employees at PT. Pos Indonesia (Persero) Bekasi as respondents, while the technique of data collection is done by distributing questionnaires, which is processed using SPSS 21.0. The research using descriptive and explanatory. The results of the regression indicate that there is influence career development towards job satisfaction and there is influence between motivatiom towards job satisfaction. Career development and motivation simultaneously influence the job satisfaction and significance. This research has figured out the score of career development and motivation on work satisfaction while the rest is influenced by the other factors.